Tantangan dan Peran BULOG di Era Industri 4.0 - Bachtiar Utomo (JURNAL PANGAN, 2020)
The management of government food stocks, especially rice, corn, and soybean commodities carried out by BULOG as a state-owned enterprise mandated by the Government to maintain food security is still experiencing problems, including the policy implementation of non-cash food aid programs, policies that are still sectoral and BULOG’s own internal operations management.In addition, BULOG’s food management is also facing the presence of Industry 4.0 challenges. With this background, this paper aims to: (i) identify problems in food management in Indonesia (ii) analyze the roles and efforts of BULOG as a food institution institution mandated by the Government in maintaining food security, and (iii) examines the efforts made by BULOG in maintaining national food security in the Industry 4.0 Era. Some food-management problems in Indonesia, namely policies on management, development, and technology of food commodities, are only focused on rice; post-harvest technology has not been implemented well; inadequate transportation infrastructure and facilities; price volatility and low efficiency of the marketing system for food products. The roles and efforts undertaken by BULOG include the integration of government rice stock management, which is considered quite useful. For this reason, the integration of government rice stock management is recommended to be continued and increased in capacity. BULOG has not been effective in managing national corn and soybean commodities. Therefore, it is recommended that the policies/assignments given to BULOG are integrated from upstream to downstream sustainably. Some regulations issued by the Government through several ministries still do not support each other. For this reason, it is suggested that a Government institution be established to handle the food sector, which is under and reports directly to the President by the mandate of the Food Law. The application of modern logistics and the development of digital technology needs to be done by BULOG to maintain national food security in the Industry 4.0 Era. Coordination and commitment must be carried out consistently from all stakeholders to develop a variety of creativity, initiatives, and innovation as well as be able to maintain the quality, quantity, and existence of BULOG in facing the agricultural Industry 4.0 Era. Abstrak Pengelolaan stok pangan pemerintah khususnya komoditas beras, jagung dan kedelai yang dilakuan oleh BULOG selaku BUMN yang diamanatkan pemerintah untuk menjaga ketahanan pangan masih mengalami permasalahan, diantaranya penerapan kebijakan program bantuan pangan non tunai, kebijakan-kebijakan yang masih bersifat sektoral dan manajemen operasional BULOG sendiri. Selain itu, pengelolaan pangan yang dilakukan BULOG juga dihadapkan dengan tantangan hadirnya Revolusi Industri 4.0. Dengan latar belakang tersebut, tulisan ini bertujuan untuk : (i) mengidentifikasi permasalahan dalam pengelolaan pangan di Indonesia; (ii) menganalisis peran dan upaya yang telah dilakukan BULOG sebagai lembaga pangan yang diamanatkan Pemerintah dalam menjaga ketahanan pangan; serta (iii) menelaah upaya yang dilakukan BULOG dalam menjaga ketahanan pangan nasional di Era Industri 4.0. Beberapa permasalahan pengelolaan pangan di Indonesia yaitu kebijakan pengelolaan, pengembangan dan teknologi komoditas pangan hanya terfokus pada beras; teknologi pasca panen belum diterapkan dengan baik; prasarana dan sarana transportasi belum memadai; ketidakstabilan harga dan rendahnya efisiensi sistem pemasaran hasil-hasil pangan. Peran dan upaya yang dilakukan BULOG di antaranya adalah integrasi pengelolaan stok beras pemerintah yang dinilai cukup efektif. Untuk itu integrasi pengelolaan stok beras pemerintah disarankan untuk diteruskan dan ditingkatkan kapasitasnya. BULOG belum efektif melakukan pengelolaan komoditas jagung dan kedelai nasional. Oleh karena itu, disarankan agar kebijakan/penugasan yang diberikan kepada BULOG terintegrasi dari hulu ke hilir bersifat keberlanjutan. Beberapa regulasi yang diterbitkan Pemerintah melalui kementerian masih belum saling mendukung antara satu dengan lainnya. Untuk itu, disarankan agar dibentuk lembaga Pemerintah yang menangani bidang pangan yang berada di bawah dan bertanggung jawab langsung kepada Presiden sesuai amanat UU Pangan. Penerapan logistik modern dan pengembangan teknologi digital perlu dilakukan BULOG untuk menjaga ketahanan pangan nasional di Era Industri 4.0. Perlu dilakukan koordinasi dan komitmen yang konsisten dari seluruh stakeholder untuk mengembangkan berbagai kreativitas, inisiatif, dan inovasi, serta mampu menjaga kualitas, kuantitas dan eksistensi BULOG dalam menghadapi era industri pertanian 4.0.